Development of Problem-Based Learning Integrated Sasambo Ethnochemistry in Colloid-Based Chemistry Teaching Materials - Andayani, Yayuk; Mutiah, Mutiah; Purwoko, Agus Abhi; Sofia, Baiq Fara Dwirani; Hidayanti, Ermia (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to determine the feasibility of product development for colloid-based chemistry teaching materials and problem-based learning integrated with Sasambo ethnochemistry to increase students' chemical literacy. This research is part of a development research procedure that adopts the 4-D model, with stages to define, design, develop, and disseminate. Test the suitability of teaching materials using a questionnaire to test content validity and construct validity. And reliability. The content and construct validity analysis technique uses the V index, while the reliability of teaching materials uses the kappa moment coefficient (K). The content and construct validity analysis results showed that the criteria were very valid, with a V index of 91.36% and 90.7%. The reliability analysis results of teaching materials obtained a kappa moment coefficient (K) of 0.88 with a very high reliability category. Based on the validity and reliability values, it is concluded that colloid-based chemistry teaching materials and problem-based learning Sasambo's integrated ethnochemistry are very suitable for learning.